Diagnóstico financiero y propuesta de mejoramiento en la Empresa de Servicios Hotel Podocarpus de la ciudad de Loja periodo 2011-2012 - Hernández Sánchez, Juan Pablo (2016)
This research work is titled, " FINANCIAL PROPOSAL FOR IMPROVING DIAGNOSIS AND SERVICE COMPANY IN HOTEL CITY PODOCARPUS LOJA PERIOD 2011-2012 ", in order to evaluate and verify the proper use of resources to support the process decision by their management and reduce investment risk through the determination of own financial risks of operational activity of the company, which was developed based on the fulfillment of specific objectives.  Apply all methodological procedures of a financial diagnosis.  Determine changes in periods, analyzing increases or decreases and their possible causes.  Apply financial ratios analyzing the strengths and weaknesses of the company Hotel Podocarpus and publicize our view.  Submit the report with proposals for improvement to the company in terms of profitability and efficient management of resources. Methodological development is based on the application of methods such as the scientific method that was the thrust of the entire research process, deductive in reviewing literature on inductive analysis of the most significant accounts, the descriptive information about the reality company; develop analytical allowed the most important part that has to do with the interpretation of the results of the analysis , all of the above leads to synthesize and summarize the information to draw conclusions and recommendations and the mathematical and statistical method use it to calculate and plot the percentages obtained in terms of participation and representativeness of the main accounts. According to the analysis applied to the company we can deduce that the same despite generating utility is not Profitable according to the investment because it keeps a margin of underperformance 5% until the last period analyzed, this means averaged company gets $ 0.04 cents for each dollar invested. Finally the directors of the Company are advised to implement the recommendations and proposed improvements result of research that will contribute to improving the administrative, financial and economic management, which in turn is useful for decision making.